Role of digital volumetric tomography in assessing morphological variations in condyle and temporal components of patients with asymptomatic temporomandibular joint - Shruthi S Hegde; Gayathri S Rao; Atul P Sattur; Kirty R Nandimath; Rajeeth S Shetty; Medhini Madi (Wolters Kluwer Medknow Publications, 2019)
Background: Radiographic features of remodeling are difficult to analyze. This has led to the popularity of using digital volumetric tomography (DVT) for temporomandibular joint (TMJ) imaging. To understand variations in normal anatomy and morphology of the condyle and temporal components of the TMJ, it is necessary to differentiate normal variant from pathology. Methods: A total of 160 condyle and temporal components of TMJ in patients with asymptomatic TMJ were assessed by two observers using orthopantomograph (OPG) and compared with DVT using axial, coronal, and sagittal sections for the different condylar and temporal changes separately. Different relationship between variables were evaluated and statistically analyzed. Results: The assessment made by two observers showed agreement between two observers for OPG and DVT (P < 0.05). A significant increase in occurrence of remodeling changes was observed with increase in age in both condyle and temporal components. A significant difference was observed between male and female in condylar and temporal changes also among the right and left sides. Remodeling changes were detected more accurately in DVT compared with OPG. The common bony changes seen were flattening followed by concavity and osteophytes. There is a significant difference in detecting these changes. Conclusion: Knowledge of morphologic variability in the TMJ is of utmost important to differentiate normal variant from pathology which would help in arriving at proper diagnosis. A more accurate and authentic information on condylar and temporal bony changes were obtained by DVT.